2021
DOI: 10.1073/pnas.2008747118
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of plastidial isoprenoid pathway by herbivore-induced β-cyclocitral in Arabidopsis thaliana

Abstract: Insect damage to plants is known to up-regulate defense and down-regulate growth processes. While there are frequent reports about up-regulation of defense signaling and production of defense metabolites in response to herbivory, much less is understood about the mechanisms by which growth and carbon assimilation are down-regulated. Here we demonstrate that insect herbivory down-regulates the 2-C-methyl-D-erythritol-4-phosphate (MEP) pathway in Arabidopsis (Arabidopsis thaliana), a pathway making primarily met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 79 publications
2
53
0
Order By: Relevance
“…Previously, it was shown that βCC treatment enhances resistance to high light stress and regulates singlet oxygen-responsive genes. Recently, we have seen that in addition to high light, βCC treatment also develops resistance to drought stress and herbivory in tomato and Arabidopsis plants, respectively [3,10,11]. Therefore, we hypothesized that βCC plays a pivotal role in the regulation of multiple stress responses.…”
Section: Effect Of Exogenous βCc Treatment On Transcriptomic Profile Of Tomato Plantmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, it was shown that βCC treatment enhances resistance to high light stress and regulates singlet oxygen-responsive genes. Recently, we have seen that in addition to high light, βCC treatment also develops resistance to drought stress and herbivory in tomato and Arabidopsis plants, respectively [3,10,11]. Therefore, we hypothesized that βCC plays a pivotal role in the regulation of multiple stress responses.…”
Section: Effect Of Exogenous βCc Treatment On Transcriptomic Profile Of Tomato Plantmentioning
confidence: 99%
“…A total of 92 DEGs that are responsive to abiotic and biotic stresses are involved in more than one stress; therefore, the same DEG is counted for each stress it is involved in. Abiotic stress-responsive DEGs include drought (20), heat (18), salinity (14), cold (11), oxidative (5), light (4), and hypoxia (2) (Figure 5c left panel). Similarly, DEGs responsive to biotic stresses include the attack of fungi (11), Enrichment analysis revealed that only the upregulated genes are annotated with GO terms belonging to the group RS.…”
Section: Exogenous βCc Treatment Specifically Upregulates Genes That Are Involved In Acclimation To the Plethora Of Environmental Stressementioning
confidence: 99%
See 3 more Smart Citations